The Process of Determining Import Duty and PDRI on Passenger Carry-Ons at Kuala Namu International Airport: The Process of Determining Import Duty and PDRI on Passenger Carry-Ons at Kuala Namu International Airport - Vina Winda Sari (Institute of Computer Science (IOCS), 2020)
Kuala Namu International Airport as the largest airport in North Sumatra has a big role for passenger and goods traffic both entering and leaving the country. The position of the city of Medan which is geographically close to neighboring countries such as Malaysia, Singapore, Thailand can be a reason for people to frequently travel abroad. As a comparison, the travel time using an airplane from Kualanamu Airport to Malaysia only takes about 2 hours. Based on existing data, the number of flights coming from abroad to Kualanamu Airport in a day is around 20 flights with an average number of passengers reaching 250 people. Therefore Customs and Excise, through one of its representative agencies that specifically supervises Kuala Namu airport, namely the Intermediate Type B Customs Supervision and Customs Service Office of Kuala Namu, plays a major role in controlling the traffic of goods and as a collector of state revenue on import taxes. Import duties and PDRI apart from functioning as a source of state revenue, also aim at protecting domestic industry, preventing the smuggling of illegal goods either because there are no documents or because the goods are not allowed to enter. Basically, every passenger who comes from abroad is given the confidence to report their luggage on the Self Assessment System by notifying them through customs documents, namely the Customs Declaration. Customs Declaration is a customs declaration on the import of goods carried by passengers or crews of transportation means.